Genetic algorithm applied to study of the economic viability of alcohol production from Cassava root from 2002 to 2013. (1st February 2016) - Campos Benvenga, Marco Antônio; Henriques Librantz, André Felipe; Curvelo Santana, José C.; Tambourgi, Elias Basile
Abstract: This work aimed to investigate the economical and environmental viability of alcohol production from cassava root from 2002 to 2013 using genetic algorithms technique, a meta-heuristic technique inspired on biological natural selection process. Amylases from Aspergillus niger have been used in starch hydrolysis processes and Saccharomyces cerevisiae yeast in fermentation process. The carbon credits obtained of alcohol production and biomass from cassava residues were used to reduce cost production. The hydrolysis occurred at temperatures ranging from 30 to 60 °C, with starch concentrations from 8.0 to 22 g/L. Results showed the best conditions for starch hydrolysis at 23.4 g/L, 61.9 °C and 111.0 min, where an yield of 84% was achieved. In this condition, though in the presence of yeast, the hydrolysis yield is close 100% and the ethanol yield was 88%, after fermentation process. An alcohol cost between 0.04 and 0.62 US$/L has been found for the studied period. In addition, the company acquires 7.8 billion of carbon credits, is environment friendly, and improves its image in the society. Results show that this meta-heuristic optimization technique could be useful for improvement of industrial alcohol production. Highlights: Use of a meta-heuristic technique to prove the viability of ethanol production from cassava. How to get carbon credits for the production of alcohol and the use of biomass in energy co-generation. How to use cassava in maintaining ethanol production.